2021
DOI: 10.48550/arxiv.2104.00593
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Semiclassical Trans-Series from the Perturbative Hopf-Algebraic Dyson-Schwinger Equations: $ϕ^3$ QFT in 6 Dimensions

Michael Borinsky,
Gerald V. Dunne,
Max Meynig

Abstract: We analyze the asymptotically free massless scalar φ 3 quantum field theory in 6 dimensions, using resurgent asymptotic analysis to find the trans-series solutions which yield the non-perturbative completion of the divergent perturbative solutions to the Kreimer-Connes Hopf algebraic Dyson-Schwinger equations for the anomalous dimension. This scalar conformal field theory is asymptotically free and has a real Lipatov instanton. In the Hopf algebraic approach we find a trans-series having an intricate Borel sin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 77 publications
(232 reference statements)
0
6
0
Order By: Relevance
“…Broadhurst and Kreimer showed that in this approach the perturbative expansion of the anomalous dimension γ(a) is characterized by a quartically nonlinear third order ODE for γ(a) [35]. The resurgent trans-series structure of this function has recently been analyzed in detail in [36,37], revealing an intricate Borel Riemann surface structure. On the first sheet there is a single dominant Borel branch point singularity with exponent 1 12 , in addition to two further resonant collinear Borel singularities, and all three of these singularities are repeated in integer multiples.…”
Section: Renormalization In Quantum Field Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Broadhurst and Kreimer showed that in this approach the perturbative expansion of the anomalous dimension γ(a) is characterized by a quartically nonlinear third order ODE for γ(a) [35]. The resurgent trans-series structure of this function has recently been analyzed in detail in [36,37], revealing an intricate Borel Riemann surface structure. On the first sheet there is a single dominant Borel branch point singularity with exponent 1 12 , in addition to two further resonant collinear Borel singularities, and all three of these singularities are repeated in integer multiples.…”
Section: Renormalization In Quantum Field Theorymentioning
confidence: 99%
“…Here we show that if noise is introduced to this computation, the result is dominated by the leading Borel singularity, so the slope relating the breakdown order N c to the logarithm of the noise strength, as in (34), can be well approximated by the one-cut situation. of the anomalous dimension in the Hopf algebraic analysis of the ϕ 3 scalar quantum field theory in 6 dimensions [35,36]. The blue dots show the average of multiple realizations of the random noise, and the blue line shows the general one-cut scaling relation in (18).…”
Section: Renormalization In Quantum Field Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…a trans-series-like ansatz; see e.g. the recent papers [27,28] for trans-series solutions to differential equations.…”
Section: Resummation Of Ladmentioning
confidence: 99%
“…While it is known that there is information encoded in such asymptotic growth rates[46], it is out of scope for our present purposes, as we will obtain accurate resummations with only a handful terms.…”
mentioning
confidence: 99%